Analysis of Coal Quality on Mining Front and Ship Loading in East Kalimantan Province: Evaluasi Kualitas Batubara pada Front Penambangan dan Ship Loading di Provinsi Kalimantan Timur - La Ode Muh Yazid Amsah; L.M. Hilman Kurnia; Anna Irada La Ode Malim (JURNAL GEOCELEBES, 2022)
This study aims to determine the quality of coal on the mining front and ship loading. The method used consists of literature study, sample collection and processing and data analysis using proximate analysis. The results of the analysis on the mining front obtained ash content 2.8%, total moisture 13.12%, volatile matter 39%, total sulfur 0.23%, fixed carbon 48%, calorie value 5.812 Kcal/Kg. On ship loading obtained ash content 3.89%, total moisture 14.15%, volatile matter 43.04%, fixed carbon 46%, total sulfur 0.25%, and calorie value 5.365 Kcal/Kg. The very different calorific value of 7.69% is influenced by changes in the total water content and ash content. This indicates a significant decline in coal quality.